Reduction of Background Fluorescence from Impurities in Protein Samples for Raman Spectroscopy - Corujo, Marco Pinto; Michal, Pavel; Wesson, Rod; Amarasinghe, Don Praveen; Rodger, Alison; Chmel, Nikola P. (Journal of Spectroscopy, 2022)
Background fluorescence remains the biggest challenge in Raman spectroscopy because of the consequent curvature of the baseline and the degradation of the signal-to-noise ratio of the Raman signal. While the concentrations of the fluorophore impurities are usually too low to be detected by other analytical methods, they are often sufficient to prevent Raman data collection. Among the different existing methods to remove the fluorescence signal, photobleaching remains the most popular due to its simplicity. However, using the spectrometer laser to photobleach is far from optimal. Most commercially available instruments have little or no choice of wavelength, and their output powers are in many cases not suitable for highly fluorescent samples such as those from biological systems (e.g., proteins). In this article, we assess practical aspects of photobleaching such as the apparent reversibility of the process and the effect of convection currents due to what we speculate to be temperature gradients across the bulk of the solution. We also introduce an affordable custom made external photobleaching unit with a choice of excitation wavelength and demonstrate its viability with a highly fluorescent bovine serum albumin protein solution, which had proved most challenging for Raman spectroscopy as it contained ∼10% w/w impurities.